Etika Islam dalam Penerapan Sains: Kajian Islam dan Sains - Salman; Derlicia Utami; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to describe the concept of Islamic ethics in the development of science, identify and analyze the principles of Islamic ethics relevant to the application of modern science, explain the implementation of Islamic ethics in various fields of contemporary science, as well as identify challenges and offer solutions in the application of Islamic ethics to modern science. The method used is library research with a descriptive-analytical approach to literature related to Islamic ethics and science. The results show that Islamic ethics is a value system derived from the Qur'an and Hadith that regulates all aspects of human life. The relevant principles of Islamic ethics include tawhid (monotheism), khilafah (stewardship), amanah (trust), maslahah (public interest), and mizan (balance). The application of Islamic ethics in bioethics, environmental ethics, artificial intelligence, and academic integrity demonstrates the relevance of Islam in addressing the ethical crisis of modern science. The challenges faced include the dichotomy of knowledge, value relativism, and the dominance of the Western scientific paradigm. Solutions offered include the Islamization of knowledge, interdisciplinary dialogue, and strengthening the Muslim scientific community.